An assessment framework for the transformation of mobility 4.0 in smart cities - ÖZTEMEL, ERCAN (MDPI, 2021)
Investing in digital transformation turns out to be a strategic action to tackle contemporary issues and to improve competitiveness for enterprises. The high variability of options in the digital transformation process enforces a higher complexity level in configuring and setting up objectives and goals based on cities’ needs; hence, a systematic approach is required to assist decision makers for better and sustainable transformation. A reference model is described in this paper to support decision makers with comprehensive assessment data for digital transformation cities transport. The proposed reference model assesses the cities based on digital transformation of transport services to assist policy makers for better decisions in transforming the Mobility 4.0. The proposed model in this study functions as a knowledge‐based systematic framework for assessing the capa-bilities of the cities, diagnosing their needs under given circumstances and identifying the best fit-ting workflow for digital transformation of urban transportation systems and related services. The reference model takes on board a group of smart city indices with respective assessment criteria in determining a smartness level of transportation components. A conceptual 4‐tier smartness scale has been proposed to establish a consistent assessment subject to cities circumstances in many re-spects. The reference model has been formalised into a mathematical model to characterise the as-sessments. The mathematical model encompasses strategic assessments by experts to identify pri-orities of investments in the digitalization process, which are aligned with strategic goals and policies of cities’ management. © 2021 by the authors. Li-censee MDPI, Basel, Switzerland.
Keywords: Assessment of smartness level; Digital transformation; Digitalisation; Mathematical phrase; Mobility 4.0; Reference model; Smart city